Comparative Study Of In Vivo And In Vitro Methods In Determining Protein Digestibility Of Feeds For Bagrid Catfish, Mystus Nemurus - Syed Muhammad, Sharifah Rahmah (2009)
The reliability study of the in vitro methods in relation to the in vivo method was conducted to assess the protein digestibility of experimental diets formulated at 35% protein and 15% lipid with 0 to 60% increasing protein substitution of fishmeal by soybean meal for bagrid catfish, Mystus nemurus. Kajian tentang kebolehpercayaan kaedah in vitro berbanding kaedah in vivo telah dijalankan untuk menentukan keterhadaman protein bagi diet kajian yang diformulasikan supaya mengandungi 35% protein dan 15% lipid bagi penggantian protein daripada serbuk ikan dengan serbuk kacang soya sebanyak 0 hingga 60% untuk ikan baung, Mystus nemurus